Earth & sky - Crewe, Megan (Skyscape, 2014)
Seventeen-year-old Skylar has been haunted for as long as she can remember by fleeting yet powerful sensations that something is horribly wrong. But despite the visions of disaster that torment her, nothing ever happens, and Sky's beginning to think she's crazy. Then she meets a mysterious, otherworldly boy named Win and discovers the shocking truth her premonitions have tapped into: that our world no longer belongs to us. For thousands of years, life on Earth has been at the mercy of alien scientists who care nothing for humans and are using us as the unwitting subjects of their time-manipulating experiments. Win belongs to a rebel faction seeking to put a stop to it, and he needs Skylar's help to save the world and keep the very fabric of reality together.